Choroid plexus‐derived miR‐204 regulates the number of quiescent neural stem cells in the adult brain. (15th July 2019) - Lepko, Tjasa; Pusch, Melanie; Müller, Tamara; Schulte, Dorothea; Ehses, Janina; Kiebler, Michael; Hasler, Julia; Huttner, Hagen B; Vandenbroucke, Roosmarijn E; Vandendriessche, Charysse; Modic, Miha; Martin‐Villalba, Ana; et al.
Abstract: Regulation of adult neural stem cell (NSC) number is critical for lifelong neurogenesis. Here, we identified a post‐transcriptional control mechanism, centered around the microRNA 204 (miR‐204), to control the maintenance of quiescent (q)NSCs. miR‐204 regulates a spectrum of transcripts involved in cell cycle regulation, neuronal migration, and differentiation in qNSCs. Importantly, inhibition of miR‐204 function reduced the number of qNSCs in the subependymal zone (SEZ) by inducing pre‐mature activation and differentiation of NSCs without changing their neurogenic potential. Strikingly, we identified the choroid plexus of the mouse lateral ventricle as the major source of miR‐204 that is released into the cerebrospinal fluid to control number of NSCs within the SEZ. Taken together, our results describe a novel mechanism to maintain adult somatic stem cells by a niche‐specific miRNA repressing activation and differentiation of stem cells. Synopsis: Systemic niche control in adult neurogenesis remains incompletely understood. Here, miR‐204 is shown to be transferred from the choroid plexus to neural stem cells (NSC) to maintain their undifferentiated state, revealing a long‐distance, post‐transcriptional fate control mechanism. Quiescent NSCs of the subependymal zone exhibit high mRNA, but not protein, levels of neurogenic fate determinants. Translation of neurogenic mRNAs is controlled by miR‐204. Choroid plexus epithelium secretes miR‐204 within extracellular vesicles into the cerebrospinal fluid, regulating NSC maintenance. Abstract : Neurogenic versus stem cell fate is controlled by long‐distance transfer of secreted miR‐204.